A method for laser marking a two-dimensional code on a pure titanium surface

By laser prescanning and marking of pure titanium surfaces, combining the mixed coating of heptafluorotrichlorosilane and n-heptane, the identification problem of QR codes in the prior art under oil and water contact was solved, and the problem of identification of QR codes in the prior art was achieved. Super hydrophobic and anti-oil effects improve the reading performance and service life of QR codes.

CN114178709BActive Publication Date: 2024-12-20SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111644809.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2024-12-20
Estimated Expiration
2041-12-29

AI Technical Summary

Technical Problem

The lack of laser marking methods for anti-oil and superhydrophobic QR codes in the prior art makes it difficult to identify the QR codes when water contact and oil stains are attached.

Method used

The surface of the pure titanium substrate is pre-scanned to form a QR code area, and then the QR code structure is engraved with laser, and the superhydrophobic/oleophobic properties are prepared by mixing heptadecafluorotrichlorosilane with n-heptane. Reagents are evenly applied to the QR code surface to improve oil stain protection and superhydrophobicity.

Benefits of technology

By improving the roughness and hydrophilicity of the QR code area, the coating's anti-oil and superhydrophobic properties are enhanced, and the QR code reading performance is significantly improved. The process is simple, and it does not affect the original marking process and the coating is stable. Good performance and long service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114178709B_ABST
    Figure CN114178709B_ABST
Patent Text Reader

Abstract

The invention discloses a method for laser marking a two-dimensional code on a pure titanium surface. The method comprises the following steps: step 1, pre-scanning the surface of a pure titanium substrate by laser to obtain a pre-scanning area of ​​a to-be-marked two-dimensional code; step 2, marking the to-be-marked two-dimensional code by laser in the pre-scanning area of ​​the to-be-marked two-dimensional code; step 3, mixing heptadecafluorotrichlorosilane with n-heptane to prepare a reagent with super-hydrophobic / oleophobic properties; step 4, uniformly coating the reagent with super-hydrophobic / oleophobic properties on the surface of the two-dimensional code laser-marked in step 2, so as to obtain a result of laser marking the two-dimensional code on the pure titanium surface. The method realizes the anti-oil and super-hydrophobic properties of the two-dimensional code area and has little influence on the reading performance of the two-dimensional code itself; the process is relatively simple, and basically does not affect the entire process of two-dimensional code marking under the original process; the anti-oil and super-hydrophobic coating has good stability and a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser marking, and in particular relates to a two-dimensional code laser marking method for a pure titanium surface. Background Art

[0002] At present, with the development of industrial Internet of Things, Data Matrix code and direct part identification technology have been widely used in the identification field of aviation, aerospace and light industrial machinery parts and components; however, the materials for marking QR codes are often corroded and adhered to oil due to long-term contact with water in the environment, making them difficult to identify; although the existing laser marking technology for QR codes is relatively mature, there is no laser marking method for oil-proof super-hydrophobic QR codes. Summary of the invention

[0003] In view of the technical problems existing in the prior art, the present invention provides a method for laser marking a two-dimensional code on a pure titanium surface to solve the technical problem that there is no laser marking method for anti-oil and super-hydrophobic two-dimensional code in the prior art.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is:

[0005] The present invention provides a method for laser marking a two-dimensional code on a pure titanium surface, comprising the following steps:

[0006] Step 1: Use laser to pre-scan the surface of the pure titanium substrate to obtain a pre-scan area to be marked with a two-dimensional code;

[0007] Step 2: Use laser to mark the QR code in the pre-scanned area of ​​the QR code to be marked;

[0008] Step 3, mixing heptadecafluorotrichlorosilane with n-heptane to prepare a reagent having super hydrophobic / oleophobic properties;

[0009] Step 4: uniformly coating the super-hydrophobic / oleophobic reagent on the surface of the two-dimensional code laser-marked in step 2, thereby obtaining the two-dimensional code laser-marking result on the pure titanium surface.

[0010] Furthermore, in step 1, before the laser is used to pre-scan the surface of the pure titanium substrate, a surface treatment operation is also performed on the surface of the pure titanium substrate;

[0011] The surface treatment operation is as follows:

[0012] The surface of the pure titanium substrate is polished so that the roughness of the polished pure titanium substrate surface is less than Ra3.2; then, the polished pure titanium substrate is placed in anhydrous ethanol, ultrasonically cleaned, and dried to obtain a surface-treated pure titanium substrate.

[0013] Furthermore, in step 1, during the pre-scanning process of the pure titanium substrate surface using laser, the power of the laser is 2-5 W, the filling line spacing is 0.03-0.05 mm, the scanning speed is 100-300 mm / s, and the frequency is 30-50 KHz.

[0014] Furthermore, in step 1, the pre-scanning area of ​​the two-dimensional code to be marked is a square silver-white area formed on the surface of the pure titanium substrate; the side length of the square silver-white area is 1.2 times the side length of the two-dimensional code to be marked.

[0015] Furthermore, in step 2, in the pre-scan area of ​​the two-dimensional code to be marked, in the process of using laser to mark the two-dimensional code to be marked, the power of the laser is 8-12W, the filling line spacing is 0.01-0.05mm, the scanning speed is 100-300mm / s, and the frequency is 30-60KHz.

[0016] Furthermore, in step 2, the two-dimensional code to be marked by laser marking is a two-dimensional code structure that is black on the surface of the pre-scan area of ​​the two-dimensional code to be marked.

[0017] Furthermore, in step 3, the process of mixing heptadecafluorotrichlorosilane with n-heptane to prepare a reagent having super hydrophobic / oleophobic properties is as follows:

[0018] Heptadecafluorotrichlorosilane and n-heptane are mixed in a volume ratio of (200-400):1, placed in a sealed container, and magnetically stirred to obtain the reagent having super-super hydrophobic / oleophobic properties.

[0019] Furthermore, during the magnetic stirring process, the stirring temperature is 35-40° C., the stirring rate is 300-400 r / min, and the stirring time is 4-6 h.

[0020] Furthermore, in step 4, the super-hydrophobic / oleophobic reagent is evenly coated on the surface of the two-dimensional code laser-marked in step 2, with coating once every 8-10 seconds, repeated 5-8 times, and left to stand for 3-5 minutes.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention provides a two-dimensional code laser marking method on a pure titanium surface, by laser pre-scanning the surface of the pure titanium substrate, the roughness of the two-dimensional code area is improved, and the adhesion and wettability of the coating layer applied later are paved; the laser marking of the black module of the two-dimensional code is carried out after the laser pre-scanning process, and the hydrophilicity of the black module area is enhanced, and the anti-oil super-hydrophobicity of the subsequent coating is further improved. The foundation is laid, and the transparent coating coating and post-treatment carried out on the two-dimensional code laser marking area have both realized the anti-oil and super-hydrophobicity of the two-dimensional code area, and the reading performance of the two-dimensional code itself is less affected. The whole process is relatively simple, and the whole process of the two-dimensional code marking under the original process is basically not affected, and it is easy to operate, and the anti-oil super-hydrophobic coating has good stability and long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a flow chart of the method for laser marking a two-dimensional code on a pure titanium surface according to the present invention;

[0024] Figure 2 The water contact angle on the surface of the pure titanium substrate that has been subjected to laser pre-scanning treatment and coated with a super-hydrophobic / oleophobic agent in Example 1;

[0025] Figure 3 The oil contact angle on the surface of the pure titanium substrate that has been subjected to laser pre-scanning treatment and coated with a super-hydrophobic / oleophobic agent in Example 1;

[0026] Figure 4 The water contact angle of the white module in the two-dimensional code laser marking result on the pure titanium surface described in Example 1;

[0027] Figure 5 The water contact angle of the black module in the two-dimensional code laser marking result on the pure titanium surface described in Example 1;

[0028] Figure 6 The oil contact angle on the surface of the pure titanium substrate coated with the super hydrophobic / oleophobic agent in Example 1;

[0029] Figure 7 is the oil contact angle of the white module in the result of the two-dimensional code laser marking on the pure titanium surface described in Example 1;

[0030] Figure 8 It is the oil contact angle of the black module in the two-dimensional code laser marking result on the pure titanium surface described in Example 1. DETAILED DESCRIPTION

[0031] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail in the following specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0032] As attached Figure 1 As shown, the present invention provides a method for laser marking a two-dimensional code on a pure titanium surface, comprising the following steps:

[0033] Step 1: Take a pure titanium plate with a thickness of 0.7-1.0 mm as a pure titanium substrate sample; then perform surface treatment on the surface of the pure titanium substrate to obtain a pure titanium substrate after surface treatment; wherein the surface treatment operation is specifically as follows:

[0034] The surface of the pure titanium substrate is polished with sandpaper so that the roughness of the polished pure titanium substrate surface is less than Ra3.2; then, the polished pure titanium substrate is placed in anhydrous ethanol, ultrasonically cleaned, and dried to obtain the pure titanium substrate after surface treatment; wherein the ultrasonic cleaning time is 5-10 minutes; in the drying process, the pure titanium substrate after ultrasonic cleaning is placed in an electric blast drying oven and dried for more than 5 minutes.

[0035] Step 2: Use laser to pre-scan the surface of the pure titanium substrate to obtain the pre-scan area for the two-dimensional code to be marked; wherein, in the process of using laser to pre-scan the surface of the pure titanium substrate, the power of the laser is 2-5W, the spacing between the filling lines is 0.03-0.05mm, the scanning speed is 100-300mm / s, and the frequency is 40-50KHz. The pre-scan area for the two-dimensional code to be marked is a square silver-white area formed on the surface of the pure titanium substrate; the side length of the square silver-white area is 1.2 times the side length of the two-dimensional code to be marked; that is, the side length of the square silver-white area is 30-50mm.

[0036] Step 3: Use laser to mark the two-dimensional code to be marked in the pre-scan area of ​​the two-dimensional code to be marked; wherein the power of the laser is 8-12W, the filling line spacing is 0.01-0.05mm, the scanning speed is 100-300mm / s, and the frequency is 30-60KHz; the two-dimensional code to be marked by the laser is a black two-dimensional code structure on the surface of the pre-scan area of ​​the two-dimensional code to be marked.

[0037] In the present invention, according to the size of the static contact angle on the surface of the pure titanium specimen after laser marking, an orthogonal test method is adopted to carry out orthogonal tests on the laser power, filling line spacing, scanning speed and frequency, and the test environment is an atmospheric atmosphere; according to the orthogonal test, when the static contact angle on the surface of the pure titanium substrate is a minimum of 6°, the laser power is 10w, the filling line spacing is 0.03mm, the scanning speed is 200mm / s, and the frequency is 45KHz, which are the optimal laser process parameters.

[0038] In the present invention, the laser marking process adopts a fiber laser marking machine, which is a fiber laser marking machine developed by Zhejiang Shengshi Laser Technology Co., Ltd., model: HSGQ-20W; the contact angle measuring instrument is a contact angle measuring instrument developed and produced by German dataphysics company, model: OCA200.

[0039] Step 4: Place the pure titanium substrate with the laser-marked QR code in anhydrous ethanol and perform ultrasonic cleaning for 5 to 10 minutes; then, place it in an electric blast drying oven and dry it for more than 5 minutes.

[0040] Step 5, heptadecafluorotrichlorosilane and n-heptane are mixed in a volume ratio of (200-400): 1, placed in a sealed container, and magnetically stirred to obtain a reagent having super-super hydrophobic / oleophobic properties; wherein, during the magnetic stirring process, the stirring temperature is 35-40° C., the stirring frequency is 300-400 r / min, and the stirring time is 4-6 h.

[0041] In the present invention, the optimal ratio of heptadecafluorotrichlorosilane and n-heptane is obtained by uniform test; wherein the optimal ratio is heptadecafluorotrichlorosilane: n-heptane = (200-400): 1

[0042] Step 6: evenly coat the super-hydrophobic / oleophobic reagent on the surface of the two-dimensional code laser-marked in step 3, thereby obtaining the two-dimensional code laser-marked result on the pure titanium surface; wherein, during the even coating process, coating is performed once every 8-10 seconds, and the coating operation is repeated 5-8 times, and the mixture is allowed to stand for 3-5 minutes.

[0043] Example 1

[0044] This embodiment 1 provides a method for laser marking a two-dimensional code on a pure titanium surface, which specifically includes the following steps:

[0045] Step 1: Preparation and pretreatment of pure titanium substrate:

[0046] Step 11, taking a pure titanium sheet with a thickness of 1 mm as a pure titanium substrate for standby use;

[0047] Step 12: polish the pure titanium substrate in step 11 with sandpaper so that the surface roughness of the polished pure titanium substrate is less than Ra3.2; then, place the polished pure titanium substrate in anhydrous ethanol for ultrasonic cleaning for 5 minutes to remove impurities on the surface in preparation for subsequent laser processing;

[0048] Step 13, use laser to pre-scan the surface of the pure titanium substrate to obtain a pre-scan area to be marked with a two-dimensional code; wherein, in the process of using laser to pre-scan the surface of the pure titanium substrate, the laser power is 2W, the filling line spacing is 0.03mm, the scanning speed is 100mm / s, and the frequency is 40KHz; the pre-scan area to be marked with a two-dimensional code is a square silver-white area formed on the surface of the pure titanium substrate; the side length of the square silver-white area is 30mm.

[0049] Step 2: Laser marking:

[0050] Step 21, in the pre-scanning area of ​​the two-dimensional code to be marked, use laser to mark the two-dimensional code to be marked; wherein the power of the laser is 8W, the filling line spacing is 0.01mm, the scanning speed is 100mm / s, and the frequency is 30KHz; the two-dimensional code to be marked by the laser is a two-dimensional code structure that is black on the surface of the pre-scanning area of ​​the two-dimensional code to be marked;

[0051] Step 22: Place the pure titanium substrate with the laser-marked QR code in anhydrous ethanol and perform ultrasonic cleaning for 5 minutes; then, place it in an electric blast drying oven and dry it for 5 minutes.

[0052] Step 3: Preparation of a reagent having super hydrophobic / oleophobic properties:

[0053] Add 300 mL of n-heptane solution to a 500 mL beaker, then add 1 mL of heptadecafluorotrichlorosilane, seal the bottle mouth with plastic wrap, place it on a magnetic stirrer, stir at 38 ° C, stir at a frequency of 300 r / min, and stir for 4 hours to obtain a reagent with super hydrophobic / oleophobic properties.

[0054] Step 4: Apply the reagent:

[0055] The prepared super-hydrophobic / oleophobic reagent is evenly coated on the surface of the two-dimensional code laser-marked in step 2, thereby obtaining the two-dimensional code laser-marking result on the pure titanium surface; wherein the coating process is specifically as follows: apply once every 8 seconds, repeat the coating operation 5-8 times, and let stand for 3 minutes.

[0056] Test result description:

[0057] In this embodiment, castor oil and tap water are used to measure the water contact angle and oil contact angle of the two-dimensional code laser marking results on the pure titanium surface; as shown in the attached Figure 2-8As shown, the experiment shows that the static contact angle (water) of the black QR code prepared with a hydrophobic and oil-transmitting film and laser treated is increased from 18.6° to 157° compared with the ordinary QR code, and the hydrophobic performance is increased by 9.8 times, achieving a super hydrophobic effect. The static contact angle (oil) is increased from 16.9° to 134.5°, and the oleophobic performance is increased by 7.9 times, and the oleophobic effect is also significantly improved.

[0058] Example 2

[0059] This embodiment 2 provides a method for laser marking a two-dimensional code on a pure titanium surface, which specifically includes the following steps:

[0060] Step 1: Preparation and pretreatment of pure titanium substrate:

[0061] Step 11, taking a pure titanium sheet with a thickness of 0.7 mm as a pure titanium substrate for standby use;

[0062] Step 12: polish the pure titanium substrate in step 11 with sandpaper so that the surface roughness of the polished pure titanium substrate is less than Ra3.2; then, place the polished pure titanium substrate in anhydrous ethanol for ultrasonic cleaning for 8 minutes to remove impurities on the surface in preparation for subsequent laser processing;

[0063] Step 13, use laser to pre-scan the surface of the pure titanium substrate to obtain a pre-scan area to be marked with a two-dimensional code; wherein, in the process of using laser to pre-scan the surface of the pure titanium substrate, the laser power is 3W, the filling line spacing is 0.05mm, the scanning speed is 200mm / s, and the frequency is 45KHz; the pre-scan area to be marked with a two-dimensional code is a square silver-white area formed on the surface of the pure titanium substrate; the side length of the square silver-white area is 40mm.

[0064] Step 2: Laser marking:

[0065] Step 21, in the pre-scanning area of ​​the two-dimensional code to be marked, use laser to mark the two-dimensional code to be marked; wherein the power of the laser is 10W, the filling line spacing is 0.03mm, the scanning speed is 200mm / s, and the frequency is 45KHz; the two-dimensional code to be marked by the laser is a two-dimensional code structure that is black on the surface of the pre-scanning area of ​​the two-dimensional code to be marked;

[0066] Step 22: Place the pure titanium substrate with the laser-marked QR code in anhydrous ethanol and perform ultrasonic cleaning for 8 minutes; then, place it in an electric blast drying oven and dry it for 10 minutes.

[0067] Step 3: Preparation of a reagent having super hydrophobic / oleophobic properties:

[0068] Add 300 mL of n-heptane solution to a 500 mL beaker, then add 1 mL of heptadecafluorotrichlorosilane, seal the bottle mouth with plastic wrap, place it on a magnetic stirrer, stir at 38°C, at a frequency of 350 r / min, for 5 hours, to obtain a reagent with super hydrophobic / oleophobic properties.

[0069] Step 4: Apply the reagent:

[0070] The prepared super-hydrophobic / oleophobic reagent is evenly coated on the surface of the two-dimensional code laser-marked in step 2, thereby obtaining the two-dimensional code laser-marking result on the pure titanium surface; wherein the coating process is specifically as follows: apply once every 9 seconds, repeat the coating operation 5-8 times, and let stand for 5 minutes.

[0071] Laser pretreatment removes the oxide layer and other attached stains on the surface of the substrate to make the surface rougher of the titanium plate. Then, a laser with specific parameters is used for QR code marking to change the surface micromorphology and enhance the hydrophilicity. The static contact angles of oil and water on the surface of the black and white modules of the QR code are measured respectively. It is found that the static contact angles of oil and water in the black module are lower than those in the white module and lower than 50°, indicating that the hydrophilicity is relatively high. Then, a layer of super-hydrophobic / oleophobic film is prepared on the surface of the QR code. It is found that the static contact angle of oil exceeds 100° to achieve an oleophobic effect, and the static contact angle of water exceeds 160° to achieve a super-hydrophobic effect.

[0072] Example 3

[0073] This embodiment 3 provides a method for laser marking a two-dimensional code on a pure titanium surface, which specifically includes the following steps:

[0074] Step 1: Preparation and pretreatment of pure titanium substrate:

[0075] Step 11, taking a pure titanium sheet with a thickness of 1 mm as a pure titanium substrate for standby use;

[0076] Step 12: polish the pure titanium substrate in step 11 with sandpaper so that the surface roughness of the polished pure titanium substrate is less than Ra3.2; then, place the polished pure titanium substrate in anhydrous ethanol for ultrasonic cleaning for 5 minutes to remove impurities on the surface in preparation for subsequent laser processing;

[0077] Step 13, use laser to pre-scan the surface of the pure titanium substrate to obtain a pre-scan area to be marked with a two-dimensional code; wherein, in the process of using laser to pre-scan the surface of the pure titanium substrate, the laser power is 5W, the filling line spacing is 0.05mm, the scanning speed is 300mm / s, and the frequency is 50KHz; the pre-scan area to be marked with a two-dimensional code is a square silver-white area formed on the surface of the pure titanium substrate; the side length of the square silver-white area is 50mm.

[0078] Step 2: Laser marking:

[0079] Step 21, in the pre-scanning area of ​​the two-dimensional code to be marked, use laser to mark the two-dimensional code to be marked; wherein the power of the laser is 12W, the filling line spacing is 0.05mm, the scanning speed is 300mm / s, and the frequency is 60KHz; the two-dimensional code to be marked by the laser is a two-dimensional code structure that is black on the surface of the pre-scanning area of ​​the two-dimensional code to be marked;

[0080] Step 22: Place the pure titanium substrate with the laser-marked QR code in anhydrous ethanol and perform ultrasonic cleaning for 10 minutes; then, place it in an electric blast drying oven and dry it for 10 minutes.

[0081] Step 3: Preparation of a reagent having super hydrophobic / oleophobic properties:

[0082] Add 400 mL of n-heptane solution to a 500 mL beaker, then add 1 mL of heptadecafluorotrichlorosilane, seal the bottle mouth with plastic wrap, place it on a magnetic stirrer, stir at 40°C, at a frequency of 400 r / min, for 6 hours, to obtain a reagent with super hydrophobic / oleophobic properties.

[0083] Step 4: Apply the reagent:

[0084] The prepared super-hydrophobic / oleophobic reagent is evenly coated on the surface of the two-dimensional code laser-marked in step 2, thereby obtaining the two-dimensional code laser-marking result on the pure titanium surface; wherein the coating process is specifically as follows: apply once every 10 seconds, repeat the coating operation 5-8 times, and let stand for 8 minutes.

[0085] The two-dimensional code laser marking method of the pure titanium surface described in the present invention removes the oxide layer and other attached stains on the surface of the substrate by laser pretreatment, so that the surface roughness of the titanium plate is higher, and then a laser with specific parameters is used to mark the two-dimensional code to change the surface micromorphology, so that the hydrophilicity is enhanced. The static contact angles of oil and water on the black and white modules of the two-dimensional code are measured respectively, and it is found that the static contact angles of oil and water in the black module are lower than those of the white module and lower than 60°, and the hydrophilicity is relatively high. Then a layer of super hydrophobic / oleophobic film is prepared on the surface of the two-dimensional code, and it is measured again to find that the static contact angle of oil exceeds 90° to achieve the oleophobic effect, and the static contact angle of water exceeds 150° to achieve the super hydrophobic effect. The oleophobic and hydrophobic effect is slightly lower than that of Example 2, which may be due to the large laser power and the wide filling line spacing of the two-dimensional code, which makes the micromorphology of the two-dimensional code rougher, so the hydrophobic and oleophobic effect is slightly reduced; in the present invention, the water contact angle has exceeded 150° to reach the super hydrophobic standard, but the oil contact angle part has not reached more than 150° but has reached the oleophobic standard at more than 90°.

[0086] The above embodiment is only one of the implementation methods that can realize the technical solution of the present invention. The scope of protection claimed by the present invention is not limited only to this embodiment, but also includes changes, replacements and other implementation methods that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention.

Claims

1. A method for laser marking a two-dimensional code on the surface of pure titanium. It is characterized in that The following steps are involved: Step 1: Use laser to pre-scan the surface of the pure titanium substrate to obtain a pre-scan area to be marked with a two-dimensional code; Step 2: Use laser to mark the QR code in the pre-scanned area of ​​the QR code to be marked; Step 3, mixing heptadecafluorotrichlorosilane with n-heptane to prepare a reagent having super hydrophobic / oleophobic properties; Step 4, uniformly coating the super-hydrophobic / oleophobic reagent on the surface of the two-dimensional code laser-marked in step 2, thereby obtaining a two-dimensional code laser-marked result on the pure titanium surface; In step 1, during the pre-scanning process of the pure titanium substrate surface by laser, the power of the laser is 2-5W, the filling line spacing is 0.03-0.05mm, the scanning speed is 100-300mm / s, and the frequency is 30-50KHz; In step 2, in the pre-scan area of ​​the two-dimensional code to be marked, a laser is used to mark the two-dimensional code, and the power of the laser is 10W, the filling line spacing is 0.03mm, the scanning speed is 200mm / s, and the frequency is 45KHz; In step 3, the process of mixing heptadecafluorotrichlorosilane with n-heptane to prepare a reagent having super hydrophobic / oleophobic properties is as follows: Mixing heptadecafluorotrichlorosilane and n-heptane in a volume ratio of (200-400):1, placing the mixture in a sealed container, and performing magnetic stirring to obtain the reagent having super hydrophobic / oleophobic properties; During the magnetic stirring process, the stirring temperature is 35-40°C, the stirring rate is 300-400r / min, and the stirring time is 4-6h; In step 4, the super-hydrophobic / oleophobic reagent is evenly coated on the surface of the two-dimensional code laser-marked in step 2, and the coating operation is repeated 5-8 times every 8-10 seconds, and the mixture is allowed to stand for 3-5 minutes. In step 1, before pre-scanning the surface of the pure titanium substrate with a laser, a surface treatment operation is also performed on the surface of the pure titanium substrate; The surface treatment operation is as follows: The surface of the pure titanium substrate is polished so that the roughness of the polished pure titanium substrate surface is less than Ra3.2; then, the polished pure titanium substrate is placed in anhydrous ethanol, ultrasonically cleaned, and dried to obtain a surface-treated pure titanium substrate; In step 1, the pre-scanning area of ​​the two-dimensional code to be marked is a square silver-white area formed on the surface of the pure titanium substrate; the side length of the square silver-white area is 1.2 times the side length of the two-dimensional code to be marked.

2. A two-dimensional code laser marking method for a pure titanium surface according to claim 1, It is characterized in that In step 2, the two-dimensional code engraved by laser is a two-dimensional code structure that is black on the surface of the pre-scan area of ​​the two-dimensional code to be engraved.

Citation Information

Patent Citations

  • QR code engraving process for metal product

    CN109676262A

  • ultraphobic surface based on tungsten carbide, a process for its production and its use

    DE19860135A1